Prognostic differences in 8th edition TNM staging of esophagogastric adenocarcinoma after neoadjuvant treatment. Issue 10 (October 2018) - Sisic, Leila; Blank, Susanne; Nienhüser, Henrik; Dorr, Sara; Haag, Georg Martin; Jäger, Dirk; Bruckner, Thomas; Müller-Stich, Beat P.; Ott, Katja; Büchler, Markus W.; Ulrich, Alexis; Schmidt, Thomas
Abstract: Background: Prognostic differences between pTN- and ypTN-categories and the prognostic accuracy of the 8th edition UICC-pTNM- and AJCC-ypTNM-staging-system for esophageal and gastric adenocarcinoma are unclear. Methods: We retrospectively analyzed data of 740 patients with esophagogastric adenocarcinoma, who underwent curative surgery (344 after neoadjuvant treatment [NT]) at our institution. Survival analyses were performed according to Kaplan-Meier (log-rank test). Multivariate analyses were performed using the Cox proportional hazard model. Results: Low ypT-categories did not discriminate overall survival (ypT0: reference; ypT1: HR1.0/p = 0.909; ypT2: HR0.9/p = 0.845; ypT3: HR1.5/p = 0.184; ypT4: HR2.8/p = 0.004) and no difference was found between ypN1- and ypN2-disease (ypN0: HR0.4/p < 0.001; ypN1: reference; ypN2: HR1.1/p = 0.653; ypN3: HR1.7/p = 0.014). In esophageal adenocarcinoma the UICC-TNM- and AJCC-ypTNM-staging-system was able to predict survival for patients after NT, while in gastric cancer it failed to provide sufficient prognostic information. A simplified staging system provided better stratification after NT and was an independent prognosticator for both esophageal and gastric adenocarcinoma (stage I: reference; stage II: HR2.2/p = 0.005; stage III: HR4.1/p < 0.001). Conclusion: Prognostic value of ypTN-categories seems limited. After NT the current UICC/AJCC-staging-system is able to predict survival in esophageal adenocarcinoma, but needs to be reevaluated in gastric cancer patients and modified if needed. A novel simplified staging system might be more practicable for patients after NT.